PEMBERDAYAAN ENTREPRENEURSHIP MELALUI PRODUK KAIN TENUN MELAYU PONTIANAK - Hastiani Hastiani (STKIP PGRI SITUBONDO, 2026)
This community service program was initiated in response to the limited involvement of local adolescents in inheriting traditional weaving skills as a distinctive Malay cultural heritage of Pontianak. Implemented by a team of lecturers from the Guidance and Counseling Study Program in Gang Sambas Jaya, Batu Layang, the program aimed to strengthen community entrepreneurial competencies while enhancing adolescents’ cultural awareness and identity formation. The activities incorporated educational outreach to elementary, junior high, and senior high schools to promote the utilization of Rumah Tenun Melayu as a local wisdom–based learning resource. The program adopted training and mentoring approaches in collaboration with Kak Kurnia, founder and manager of Rumah Tenun Melayu, involving 50 weaving cadres and adolescents. The intervention covered practical weaving techniques, the development of philosophically meaningful Malay patterns, intellectual property rights literacy, and the optimization of digital marketing through social media platforms. The findings indicate increased adolescent engagement, awareness, and active participation in preserving and disseminating local woven products in digital spaces.